2020
DOI: 10.1108/acmm-08-2019-2163
|View full text |Cite
|
Sign up to set email alerts
|

Corrosion performance of steel reinforcement in concrete admixed with magnesium chloride and sulphate

Abstract: Purpose Besides with a large amount of Na+ and Cl− ions in seawater, the presence of Mg+2 and SO4−2 ions builds more complex corrosion mechanism. This paper aims to investigate the corrosion of embedded reinforcement in concrete with the environment of both Cl− and SO4−2 anions associated Mg+2 cation. Design/methodology/approach The concrete specimens were prepared by using ordinary Portland cement (OPC), and OPC blended with metakaolin (MK) for water to cementitious material ratio (w/cm) 0.48 and 0.51. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The volume of these products is significantly larger than that of the original steel bar, which leads to gradual cracking on the surface of concrete. 2Fe(OH)3+nH2O=Fe2O3•nH2O+2H2O (7) 2Fe(OH)3→Fe2O3+3H2O (8) 6Fe(OH)2+O2→Fe3O4+6H2O (9) In this study, when simulating the conditions of rebar corrosion, the well-cured RC was first immersed in an etch tank filled with 5% sodium chloride solution for two days to moisturize the concrete protective layer, establishing an electric current path. When conducting corrosion, the preembedded wire was connected to the positive terminal of the direct current power supply, and the iron mesh was connected to the negative terminal.…”
Section: Steel Bar Corrosion and Simulation Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The volume of these products is significantly larger than that of the original steel bar, which leads to gradual cracking on the surface of concrete. 2Fe(OH)3+nH2O=Fe2O3•nH2O+2H2O (7) 2Fe(OH)3→Fe2O3+3H2O (8) 6Fe(OH)2+O2→Fe3O4+6H2O (9) In this study, when simulating the conditions of rebar corrosion, the well-cured RC was first immersed in an etch tank filled with 5% sodium chloride solution for two days to moisturize the concrete protective layer, establishing an electric current path. When conducting corrosion, the preembedded wire was connected to the positive terminal of the direct current power supply, and the iron mesh was connected to the negative terminal.…”
Section: Steel Bar Corrosion and Simulation Methodsmentioning
confidence: 99%
“…They discovered that corrosion products tended to deposit within large pores located close to the steel bar, such as drainage areas and voids. Raghu et al [7] examined the corrosion of steel bar in RC structures under an environment where chloride ions and sulfate ions coexist with magnesium ions. They observed that RC structures mixed with ordinary Portland cement (OPC) and metakaolin (MK) exhibited improved resistance against corrosion.…”
Section: Introductionmentioning
confidence: 99%
“…The reason is that the building is located near to seashore. The potential of carbonation and corrosion could occur [18][19][20]. A combination of external effects from sea which a potential to sulfate is promoted to the lowering the integrity of beam 3B as compared to the other beam 3A and 4A respectively.…”
Section: Crack Detection and Upv Evaluationmentioning
confidence: 99%
“…Concrete reinforcement is crucial in bridge engineering construction, which can effectively avoid damage to the building structure affected by various factors and reduce the bridge building safety risks and safety hazards [1]. In the construction of bridge engineering, the durability and safety of the bridge-building structure should be considered comprehensively, and the concrete should be reinforced through certain technical means [2][3]. Usually, the structural strength and stiffness of the concrete structure under different loading conditions have certain differences [4].…”
Section: Introductionmentioning
confidence: 99%